2021
DOI: 10.3390/cancers13061341
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Intravenous Iron Therapy Differentially Alter the On- and Off-Tumor Microbiota in Anemic Colorectal Cancer Patients

Abstract: Iron deficiency anemia is a common complication of colorectal cancer and may require iron therapy. Oral iron can increase the iron available to gut bacteria and may alter the colonic microbiota. We performed an intervention study to compare oral and intravenous iron therapy on the colonic tumor-associated (on-tumor) and paired non-tumor-associated adjacent (off-tumor) microbiota. Anemic patients with colorectal adenocarcinoma received either oral ferrous sulphate (n = 16) or intravenous ferric carboxymaltose (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…With iron deficiency anemia tending to be unequally prevalent between right-and left-sided colorectal cancer patients, this may influence the differences observed in the tumor microbiota between locations [26]. As enteral iron therapy has been shown to alter the gut microbiota, this leaves the potential to present with differential bacterial populations compared to patients treated with parenteral iron, or those who are not iron deficient [13,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With iron deficiency anemia tending to be unequally prevalent between right-and left-sided colorectal cancer patients, this may influence the differences observed in the tumor microbiota between locations [26]. As enteral iron therapy has been shown to alter the gut microbiota, this leaves the potential to present with differential bacterial populations compared to patients treated with parenteral iron, or those who are not iron deficient [13,16].…”
Section: Discussionmentioning
confidence: 99%
“…However, as subsequently discussed by Al-Hassi et al (2018), patients with right-sided colorectal tumors more commonly develop iron deficiency anemia relative to those with left-sided tumors, hence more often requiring iron therapy [12]. Enteral iron supplementation, often given to treat anemia, has been shown to alter the colonic microbiota, potentially through increasing gut luminal iron availability for bacterial cell proliferation [13]. The occurrence of iron deficiency anemia and the use of enteral iron supplementation was not assessed by the authors in the Flemer study and has the possibility to be accountable for differences observed [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteosarcoma (OS) is the most prevalent form of malignancy affecting adolescents, occurring preferentially in males and developing at relatively high rates in individuals between the ages of 60 and 80 years [ 1 , 2 ]. While neoadjuvant chemotherapy has led to significant improvements in the duration of OS patient overall and disease-free survival (DFS), the survival of OS patients has plateaued in recent years [ 1 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed the supremacy of intravenous over per o s iron supplementation in mitigating inflammation around the tumor site by modulating the local microbial environment. The study included samples from 40 individuals, hence validation in larger cohorts is needed [ 74 ]. Nonetheless, the aforementioned studies indicate that even frequently prescribed medications such as antibiotics or iron supplementation need to be reconsidered in the context of microbiota-mediated CRC recurrence ( Figure 1 ).…”
Section: Microbiota In Crcmentioning
confidence: 99%